Mid-infrared polarization beam splitter based on square/circular hybrid air holes with wide bandwidth and ultrashort length - Zheng, Guang-ming (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
A novel mid-infrared polarization beam splitter (PBS) based on GaS is proposed. The high birefringence is achieved by using the cladding structure of alternating arrangement of square and circular air holes as well as introducing double elliptical air holes. The finite element method (FEM) is utilized to investigate the mode coupling characteristics in the proposed PBS. The results show that the highest extinction ratio of 115 dB and shortest length of only 40 μm can be realized at a wavelength of 4 μm. A wide bandwidth of 200 nm ranging from 3.9 to 4.1 μm is obtained.
Optica Applicata, Vol. 52, 2022, nr 3, s. 345-358
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; polarization beam splitter; mid-infrared; photonic crystal fiber; bandwidth; square and circular air hole